Environmentalism(s) and natural assets: challenges to extractivism in Argentina and Brazil - Wagner, Lucrecia (2013)
This paper tackles environmental conflicts generated for struggles for land and water, facing the advance of the extractive frontier -principally, monocultures and mega mining- from the action of social movements in Brazil and Argentina.Considering the currents of environmentalism which get into a dispute over the appropriation of natural commons, we will argue how social movements in Brazil and Argentina demonstrate the fallacy of the hegemonic capitalist discourse about the environmental crisis. Thus, we will consider emblematic movements in each country: the Movement of “Trabajadores Rurales Sin Tierra (MST)” of Brazil and the movements that resist the large-scale mining -or mega-mining-in Argentina. The characterization of these movements is grounded in researches that included interviews and field work in these territories of resistance.We believe that these conflicts and their social actors bring to light the inequalities inherent to the distribution of environmental impacts, which the rhetoric of sustainable development attempts to hide with its socially inclusive and environmentally friendly conception.Environmental conflicts provide the possibility of quashing the hegemonic image of an environmental crisis common to all and simultaneously, installing the discussion about the legitimate need of the appropriation of natural commons.